Patterns of initial opioid prescription and its association with short- and long-term use among opioid-naïve patients in Malaysia: a retrospective cohort study - Zin, Che Suraya; Nazar, Nor Ilyani; Abdul Rahman, Norny Syafinaz; Ahmad, Wan Rohaidah; Rani,, Nurul Sahida; Ng, Kim Swan (BMJ Publishing Group Ltd, 2019)
This study examined opioid prescription initiation patterns and their association with short- and long-term opioid use among opioid-naïve patients. Design This study was designed as a retrospective cohort study.